EXPLORING REPRODUCTIVE HEALTH RIGHTS: UNDERSTANDING OF HIGHLY EDUCATED WOMEN PARTICIPATING IN THE FAMILY PLANNING PROGRAM IN INDONESIA - Hendrawan, Rio Budi; Arsi, Antari Ayuning (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The family planning program, originally established to address the high birth rate in Indonesia, introduced additional challenges by requiring women to participate as family planning acceptors. The imposition of this condition ultimately leads to gender inequity in society due to the reproductive responsibility borne by women. This study seeks to elucidate the understanding and satisfaction of reproductive health rights among highly educated women who have chosen family planning. The research employed a qualitative methodology, utilizing exploratory in-depth interviews as the primary means of data gathering. The findings of this study indicate a deficiency in the informants' understanding of reproductive health and their rights pertaining to reproductive health. The realization of informants' reproductive health rights has not been fully achieved. The findings of this study suggest that gender inequality persists as women continue to bear the whole burden of reproductive responsibilities within the family, mostly owing to limited access to education and the perpetuation of societal prejudices.Program KB (Keluarga Berencana) yang sejatinya muncul sebagai respon atas tingginya angka kelahiran di Indonesia justru menimbulkan permasalahan baru dengan ditetapkannya perempuan sebagai akseptor KB. Penetapan ini akhirnya menciptakan ketidakadilan gender dalam masyarakat karena beban reproduksi yang diemban oleh perempuan. Penelitian ini bertujuan untuk mendeskripsikan bagaimana pengetahuan dan pemenuhan hak kesehatan reproduksi perempuan akseptor KB yang berpendidikan tinggi. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan teknik pengumpulan data berupa wawancara mendalam yang bersifat eksploratif. Hasil dari penelitian ini adalah pengetahuan tentang kesehatan reproduksi dan hak kesehatan reproduksi informan masih kurang. Pemenuhan hak kesehatan reproduksi informan juga belum terpenuhi secara maksimal. Dari hasil penelitian ini mengindikasikan bahwa ketidakadilan gender masih terjadi karena peran reproduksi dalam keluarga sepenuhnya masih dipegang oleh perempuan yang disebabkan kurangnya edukasi dan stereotipe yang berkembang dalam masyarakat.